A case report of drug resistant Tinea corporis - Kabir, Md Saiful; Begum, Wazeda; Rahman, Md Maruf Ur; Warish, Nehal (Journal of Dhaka National Medical College & Hospital, 2018)
Superfecial fungal infections of the skin are a major health problem and associated with morbidity due to chronic itching and inflammation of skin. Tinea corporis is known as ringworm, a superficial fungal infection (dermatophytosis) of the arms and legs, especially on glabrous skin. Treatment includes systemic and topical antifungals with variable duration depending upon the site of infection and the antifungal chosen. Choosing the right treatment is not always simple because of the possibility of drug interactions and drug resistance. Recently Clinical failure and relapses have been observed frequently in patients treated with antifungal drugs. Now a days, Antifungal drug resistance is becoming an emerging problem in management of fungal infections. In this article we report a case of drug resistant Tenia Corporis, its management & treatment outcome. J. Dhaka National Med. Coll. Hos. 2018; 24 (01): 44-47